Visual task difficulty and temporal influences in glare response. (January 2016) - Altomonte, Sergio; Kent, Michael G.; Tregenza, Peter R.; Wilson, Robin
Abstract: The literature suggests that glare sensation may be influenced by visual task difficulty. Previous research by the authors provided reasons to infer that the perceived level of visual discomfort may vary with time of day and be affected by temporal and personal factors. The study presented here explores the postulated relationships between visual task difficulty, temporal variables, and glare response as the day progresses. Under controlled laboratory conditions, twenty subjects were exposed to a constant artificial source luminance at four times of day and gave glare sensation votes while completing twelve visual tasks of various difficulties. Self-assessments of temporal variables (fatigue, food intake, caffeine ingestion, mood, previous daylight exposure and sky condition) were provided by test subjects together with their glare judgements. Statistical analysis of responses confirmed that the time interval between test sessions showed a direct relationship to the increased tolerance to artificial source luminance along the day. The temporal variation of glare response was found to be influenced by the difficulty in extracting information from the visual stimulus. Moreover, statistically significant and substantive evidence was detected of a direct effect of fatigue and caffeine ingestion, and an inverse influence of food intake, on reported glare sensation. Consideration of inferential results from all test sessions led to hypothesise that some temporal variables may interact with each other and significantly affect the variation of glare response at different times of day. Graphical abstract: Highlights: Influence of task difficulty and temporal variables on glare response was studied. Reported tolerance to source luminance was found to increase as the day progresses. The effect of time of day on glare response varied with task type and difficulty. A direct relation was found between glare sensation, fatigue and caffeine ingestion. Temporal variables interact with each other affecting glare response along the day.